Pseudoaneurysm of the thoracic aorta (clinical case) - Romaniuk, T.V.; Moroz , V.S.; Lekan , R.Io. (Medicni Perspektivi, 2025)
The purpose of the work is to publicize a complex clinical case of the disease – pseudoaneurysm of the thoracic aorta, based on the results of the patient's examination and treatment. Analysis of surgical treatment tactics, description of applied surgical techniques during radical surgery, the results of a clinical study of a patient with a thoracic aortic pseudoaneurysm are presented. For this purpose, echocardioscopy, coronary angiography, contrast-enhanced computed tomography, general clinical laboratory tests, and microbiological examination of biological fluids and tissues were used. Based on the diagnostic data, the primary clinical diagnosis was established: Ischemic heart disease. Stable angina pectoris, functional class III, post-infarction cardiosclerosis with hypokinesis of the posterior wall of the middle and basal segments of the left ventricle. Polytopic supraventricular extrasystole of the type of bigeminia and trigeminia. Hypertensive disease of the 2nd stage, 3rd stage. Thoracic aortic aneurysm. CHF IIa stage. A clinical case of surgical treatment of thoracic aortic pseudoaneurysm is described: the course of primary surgical treatment of thoracic aortic aneurysm (Supracoronary prosthesis of the ascending aorta, aortic valve revision. CABG (Ao-PDA) in conditions of artificial blood circulation), postoperative observation, as well as the prerequisites for the occurrence of thoracic aortic pseudoaneurysm. The course of this complication is directly described, with a description of the course of surgical treatment: Resternotomy. Elimination of prosthetic pseudoaneurysm of the ascending aorta. Plastic surgery of the distal anastomosis and plastic surgery of a linear rupture of the right ventricle in conditions of complete circulatory arrest (18°C, 38 min.), as well as the features of the postoperative period after it. Conclusions have been made that may help prevent the occurrence of thoracic aortic pseudoaneurysm and treat it more effectively. In particular, its infection was established as a factor in the cause of the defect of the distal anastomosis of the prosthesis. The described surgical technical method of peripheral cannulation with artificial blood circulation, with heart drainage, with cold arrest up to 18°C, within 38 minutes allowed to quickly localize the pseudoaneurysm of the thoracic aorta, bleeding from the defect of the distal anastomosis of the prosthesis, which occurred during resternotomy; to perform the main stage of surgical intervention – elimination of prosthetic pseudoaneurysm of the ascending aorta, plastic surgery of the distal anastomosis and plastic surgery of the linear rupture of the right ventricle.